2012
DOI: 10.1179/0093469012z.00000000020
|View full text |Cite
|
Sign up to set email alerts
|

Life and death at precolumbian Lavoutte, Saint Lucia, Lesser Antilles

Abstract: The Caribbean archaeological record requires immediate attention and protection. Development and natural forces have impacted archaeological sites, destroying or severely damaging them. The precolumbian site of Lavoutte, located in northern Saint Lucia, has been known as a major Late Ceramic Age (A.D. 1000-1500) settlement since the 1960s, but it has been damaged over the past decades by both natural and human processes. Multidisciplinary field and laboratory methodologies were implemented during a rescue proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 36 publications
0
17
0
6
Order By: Relevance
“…These combinations of conditions would have provided ready access to a wide range of environments and food resources in the immediate vicinity of the settlement. A prominent focus of previous multi-disciplinary studies at Lavoutte is bioarcheological research of the burial population including mortuary, osteological, dental, radiocarbon, and biogeochemical analysis (Hofman et al, 2012;Laffoon, 2012;Mickleburgh, 2013;Weston, 2011). Carbon-14 dating of human bone material from twelve separate individuals from Lavoutte produced median calibrated dates ranging from circa AD 1250 to 1500 and confirms that the burial population dates to the terminal Late Ceramic Age (Hofman et al, 2012).…”
Section: Archeological Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…These combinations of conditions would have provided ready access to a wide range of environments and food resources in the immediate vicinity of the settlement. A prominent focus of previous multi-disciplinary studies at Lavoutte is bioarcheological research of the burial population including mortuary, osteological, dental, radiocarbon, and biogeochemical analysis (Hofman et al, 2012;Laffoon, 2012;Mickleburgh, 2013;Weston, 2011). Carbon-14 dating of human bone material from twelve separate individuals from Lavoutte produced median calibrated dates ranging from circa AD 1250 to 1500 and confirms that the burial population dates to the terminal Late Ceramic Age (Hofman et al, 2012).…”
Section: Archeological Contextmentioning
confidence: 99%
“…These excavations recovered significant quantities of material remains including ceramics, lithic raw materials and tools, shell, coral, and animal bone, and revealed the presence of numerous features including post-holes from houses and other built structures in addition to more than 48 burials. Preliminary paleo-environmental reconstruction of the site's surroundings (Hofman et al, 2012) indicated the presence of xerophytic scrub or low woodland on the surrounding slopes including, amongst other plants, agave and several varieties of cacti. Multiple small freshwater channels drain into the bay near the site and were the locations of small mangrove swamps, remnants of which persist today.…”
Section: Archeological Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, recent research (Mickleburgh and Laffoon 2017) has demonstrated that 'Archaic' individuals from Aruba, where multiple lines of archaeological and bioarchaeological evidence have previously suggested distinct hunter-gatherer subsistence practices and highly marine-reliant diets, also possessed extremely enriched enamel δ 13 C values (−5.3 to −3.9‰). In recent years, strontium isotope ( 87 Sr/ 86 Sr) approaches have also been widely applied to studies of human and animal paleomobility, and artefact provenance studies in the Caribbean (Booden et al 2008;Giovas et al 2016;Hofman et al 2012;Hoogland, Hofman, and Panhuysen 2010;Laffoon 2012Laffoon , 2013Laffoon , 2016Laffoon et al , 2014Laffoon et al , 2015Laffoon et al , 2017Laffoon, Sonnemann et al 2016;Valcárcel Rojas et al 2011). The Caribbean region is particularly well suited to the application of the strontium isotope method owing to the geological diversity (Donovan and Jackson 1994) and hence high degree of variability and spatial pattering of bedrock and bioavailable 87 Sr/ 86 Sr. For this region, both large-scale empirical datasets and spatially explicit predictive models of regional isotope landscapes (isoscapes), of bioavailable 87 Sr/ 86 Sr have been developed (Bataille, Laffoon, and Bowen 2012;.…”
mentioning
confidence: 99%